Role of Microfinance Institutions in Women Entrepreneurship through WSHGs: Examining the Impact of Microfinance Institutions on Women Entrepreneurship and the Role of WSHGs (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women entrepreneurs play a very crucial role in the economic development of their families and their countries at large. Microfinance Institutions (MFIs) provide its members with financial and social intermediation services by WSHGs to help improve their businesses. The present paper is an attempt to focuses on issues and innovation in women entrepreneurship, growth of amount refinancing by MFIs to WSHGs and also tries to identify the relationship between MFIs and WSHGs. To check the various schemes under which the micro finance tool is apply and the progress of this program the help of various data provided by the government and other institutions is included in this study and concluded that MFIs and WSHGs shows positive relationship together, amount of refinancing by MFIs to WSHGs is year of year continuously increasing and government take new initiatives to the growth of women entrepreneurship and the result of these initiative is Bangalore have 40th and Delhi have 49th position among world top 50th cities in the dell global women entrepreneur survey 2017.